Building Better Britains? : Settler Societies in the British World, 1783-1920 - Morgan, Cecilia, 1958- (Book collections on Project MUSE., 2017)
"The effects of empires, as well as their lingering presence in today's world, have become a major preoccupation for scholars in the early twentieth-first century academy. The British Empire is of particular focus because of the rapidity and range of British imperial expansion over this period. This short book looks at the spread of settler colonies within the British Empire over the course of the 19th century, specifically those in New Zealand, Canada, South Africa, and Australia."--